THE STREAM OF CONSCIOUSNESS STUDY IN MC’EWAN’S ATONEMENT (2001) - Lina Try Astuti; Mearico Ganda Putra (Literary Criticism, 2014)
Stream of consciousness is one of ways that is used by the narrator or the author of some literary works in directing the story. Atonement is one of great literary work that is created by Ian Mc’ Ewan in 2001. In this novel shown that the stream of consciousness technique is used as the tool in presenting the story. This way is important to make the story to be understandable for the readers especially for novels and short story. Such confusing thing when we are reading some literary works without having understanding about what we read. By using descriptive qualitative method, the researcher tried to find the kind of stream of consciousness that is used by the author in presenting the story of the novel. Classifying the quotation of the story of related novel is one of many ways that is chosen by the researcher in helping the analysis of this research to determine what kind of stream of consciousness technique that is commonly used in the story of Ian Mc’ Ewan’s Atonement. After having analysis over all of the related source in the story, the researcher found that there is a tendency of the author of Atonement in using the stream of consciousness technique in presenting the story. The used technique of stream of consciousness is included to the indirect interior monologue. As said by Bickerton (78), indirect interior monologue the type of interior monologue in which an omniscient author presents unspoken material as if it were directly from the consciousness of a character and, with commentary and description, guides the reader through it. It means that, the intervention of the author of Atonement is highly abided in the story line of the novel. Keywords: Stream of Consciousness, Atonement, Indirect Interior Monologue.